Studies On Repellent And Feeding Behaviour Of House Rat, Rattus Rattus, In Response To Cinnamamide (Applied Biological Research, 2017)
Rodenticides are the preferred option to prevent rodent attacks to crop  produce. However, secondary poisoning and development of shyness and  resistance among rodents after exposure to toxic chemicals has increased the  search for plant based effective, safe and ecofriendly control methods. In present study, repellent and feeding behaviour of house rat in response to 0.4%  cinnamamide based formulation was studied using automated Ethovision video  tracking system and feed scale consumption monitor. Results revealed absence  of primary repellent effect of cinnamamide formulation but existence of its  secondary repellent effect against house rat. Repellent effect of cinnamamide  increased with time during treatment period. Moreover, during treatment  period, rats handled treated bait less frequently as compared to the untreated  bait because feeding bouts events and feeding bout time also decreased during  treatment period.
Keywords: Cinnamamide; Ethovision video tracking system; eeding behaviour; Rattus rattus; feed scale consumption monitor; repellent